STRATEGIES FOR THE DEVELOPMENT OF THE CYRIL AND METHODIUS ROUTE ON MACEDONIAN SOIL (Philological Studies, 2025)
The Cyril and Methodius Route, as a part of the Council of Europe Cultural Routes programme, established in 2013 as an international network of countries and partners, commemorates and affirms the legacy of Saints Cyril and Methodius in relation to European cultural heritage. Their educational mission left an indelible mark on the cultural heritage of the peoples of Europe. This program, dedicated to the Cultural Route of Cyril and Methodius, offers a model for scientific research and development, affirmation of European cultural heritage, cultural and educational exchange of young people in Europe, development of management in cultural tourism, etc. Ss. Cyril and Methodius’ cultural heritage has a long and deep tradition in the territory of R N. Macedonia, evident in both tangible and intangible cultural forms. The new perspectives in cultural tourism related to the Cyril and Methodius cultural heritage on Macedonian territory can be treated as both a cultural and an economic activity related to events and organized trips, aimed at exploring cultural forms such as: historical monuments, architectural complexes, as well as artistic, religious, educational and informative events of an academic nature. The original Cyril and Methodius medieval heritage on the territory of Macedonia is remarkably preserved, evident and important for the contemporary inhabitants of Europe and represents an excellent potential for cultural tourism. In the presentation, we highlight as particularly significant the strategies in the implementation of new practices in the development activities of the Saints Cyril and Methodius Route on Macedonian soil, consistent with the practices in other member countries of the Route itself.
Keywords: cultural route, Ss. Cyril and Methodius, cultural heritage, strategies, development